Experimental study on the effectiveness of inhibitors affected by high-temperature coal bodies - Xuefeng Wang; Yuhao Liu; Bing Lu; Ye Liu; Ling Qiao; Xun Zhang (Case Studies in Thermal Engineering)
The efficacy of inhibitors differs significantly between laboratory and field applications, primarily due to neglecting the impact of high-temperature coal on inhibition performance. This study evaluated CaCl2, EDTMPA, and TBHQ on coal samples heated at 30 °C, 60 °C, and 90 °C using programmed temperature ramping, Electron Paramagnetic Resonance (EPR), Fourier Transform Infrared (FTIR) spectroscopy, and thermogravimetric analysis. Results show that both CaCl2 and EDTMPA exhibit enhanced inhibition at higher temperatures. Specifically, CO content for 90-CaCl2 and 90-EDTMPA was 8.68 % and 14.96 % of that in untreated coal at 30 °C, with oxygen consumption rates of 12.78 % and 13.16 %, respectively. Functional group reductions were also observed. TBHQ showed optimal performance at 60 °C, with ignition points for 90-CaCl2, 90-EDTMPA, and 60-TBHQ delayed by 54.76 °C, 19.69 °C, and 12.33 °C, respectively, compared to untreated coal at 30 °C. These findings suggest selecting inhibitors based on coal body temperature can enhance fire prevention efficiency in mines, optimizing inhibitor use and improving mine safety.